2010
DOI: 10.1111/j.1365-2966.2010.16826.x
|View full text |Cite
|
Sign up to set email alerts
|

The rotational excitation of HCN and HNC by He: temperature dependence of the collisional rate coefficients

Abstract: Modelling of molecular emission from interstellar clouds requires the calculation of rates for excitation by collisions with the most abundant species. This paper deals with the calculation of rate coefficients for rotational excitation of the HCN and HNC molecules in their ground vibrational state in collision with He. Calculations of pure rotational (de‐)excitation cross‐sections of HCN and HNC by He were performed using the essentially exact close‐coupling method. Cross‐sections for transitions among the 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 20 publications
6
130
1
Order By: Relevance
“…The HCN/HNC abundance ratio is always above 1 and as high as 3. The determination of the HCN/HNC ratio using non-LTE analyses are likely to be unreliable due to the use of incorrect collisional excitation rates for HNC (Sarrasin et al 2010, Dumouchel et al 2010, Dumouchel et al 2011. Taking into account the new collisional excitation rates will lead to smaller HNC abundances, almost certainly leading to a HCN/HNC ratio above 1 in agreement with our simulations.…”
Section: Comparison With Observationssupporting
confidence: 80%
See 3 more Smart Citations
“…The HCN/HNC abundance ratio is always above 1 and as high as 3. The determination of the HCN/HNC ratio using non-LTE analyses are likely to be unreliable due to the use of incorrect collisional excitation rates for HNC (Sarrasin et al 2010, Dumouchel et al 2010, Dumouchel et al 2011. Taking into account the new collisional excitation rates will lead to smaller HNC abundances, almost certainly leading to a HCN/HNC ratio above 1 in agreement with our simulations.…”
Section: Comparison With Observationssupporting
confidence: 80%
“…The rotational excitation rate constant with H 2 being deduced from the one with He. However it has been shown that this approximation leads to a notable overestimation of the rotational rate constant for HNC (Sarrasin et al 2010, Dumouchel et al 2010, Dumouchel et al 2011. The use of the new rotational rate constant will lead to revised HNC/HCN abundance ratios derived from observations from values >1 to values ≤1 (Dumouchel et al 2010).…”
Section: Model Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all of our tests we generate artificial lines using RADEX and collision rates from the Leiden Lambda database (van der Tak et al 2007;Dumouchel et al 2010;Yang et al 2010). The specifics depend upon the investigation in question, but the features common to most of the models are as follows.…”
Section: Generating Linesmentioning
confidence: 99%